SPECIFICS OF THE GRAND MOTHER IMAGE TRANSFORMATION IN THE SHORT STORY “THE LOVELY LADY” BY D.H. LAWRENCE - Lyudmyla M. Kulakevych (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2022)
The article aims at analyzing the specifics of image modeling of the Lovely Lady in the short story by D.H. Lawrence, “The Lovely Lady”. The task is to distinguish the artistic components of the image of the main character. The study has been conducted using elements of motive-based, receptive-interpretive, psychoanalytic, and comparative methods of analysis. In the short story “The Lovely Lady” D.H. Lawrence artistically depicts the latent struggle for a man between a young woman/potential daughter-in-law and an old mother/future mother-in-law. The title of the story, which refers to the platonic relationship between a pretty lady and a knight without trying to know each other physically, somehow directs the perception of female confrontation not towards the reclaiming of their female space, but to a rivalry for a romantic interest. Lady Attenborough is portrayed primarily as a pretty and intelligent woman, the object of male admiration, episodes or details that would characterize her as a mother are scarce. It is worth mentioning that the lady’s idea to take seemingly unattractive Cecilia as a companion is perceived as an all-times female trick to have an ugly girlfriend by her side for the sole benefit – so that compared to her, the lady could look even more attractive to men. Attenborough’s son’s behavior shows how powerful the mother’s influence is and how weak his personality happens to be. This undeclared, unspoken competition of women for a man finds an artistic implementation in the repetitive daily situation at the dinner table, which oddly resembles a love triangle, which is always finalized with the late-night mother and son tête-à-tête time. It is emphasized that Pauline`s narcissistic love for her appearance is designed to ambiguously demonstrate her raison d’être: to always stay attractive to men. The motif of the heroine`s eternal youth is linked to the motif of vampirism, which finds realization both at the level of Pauline’s behavior and through the description of her way of life by her son. All his life, Robert has been focused exclusively on his mother, building his communication with Lady Attenborough as with a romantic partner and not the woman who gave birth to him. The incestuous nature of the mother-son relationship is metaphorically expressed on a spatial level: only Pauline and Robert live in the house, while Cecilia is given a room in another building. It is emphasized that Lady Attenborough influences her son as a destructive and even castrating force, which in turn refers to the archetype of the Great Mother, who can both bestow and destroy. The features of the lady`s appearance (she is both old and young, lovely and ugly) point to a fairy-tale mythological context, where the archetype of the Terrible Mother is most often objectified as a witch, stepmother, or mother who hates her son. Pauline`s presentation is expressed by the micro-image of Circe, which is a mythological objectification of an insidious and dangerous beauty who seeks to subdue men to her will, turning them into pigs. As Robert stays mentally inseparable from his mother, it causes his infantilism, his unwillingness, and fear of knowing another woman. In fact, it creates a conflict in his psyche. And, similar to myths and fairy tales, only with the death of his mother, Lawrence`s hero is freed from her negative influence and gets the opportunity to express his courage and behold femininity. In the short story, the author`s text is contaminated with the point of view of Cecilia as a direct participant in the events, thus presenting a woman`s view of the situation. From the standpoint of psychoanalysis, the inversion of the gender roles of Cecilia and Robert can be decoded as the subjectivation of Anima and Animus actants in relation to each other, which to some extent explains the lack of mutual erotic and aesthetic contemplation. Robert presents the deformed Cecilia`s Anima because an early orphaned girl could not afford the gender luxury of passive anticipation of a marriage proposal. Cecilia is the castrated Animus of Robert, who is forced to suppress himself due to his incestuous mental connection with his mother and unwillingness to separate from her, which is metaphorically presented through the territorial demarcation of the actants: the invited young woman is housed in a separate building. The fact that Ciss is living in the rooms above the stable, where now a car is kept, is seen as a metaphor for pushing Attenborough’s son’s healthy instincts and emotions to the margins (a car, as well as horses, are traditional markers of male energy and strength, passions and instincts). Lawrence`s short story is an artistic illustration of the destructive image of the mother, the maternal care as total control over an adult son, which causes his infantilism in life.